2006
DOI: 10.1093/hmg/ddl243
|View full text |Cite
|
Sign up to set email alerts
|

α-synuclein acts in the nucleus to inhibit histone acetylation and promote neurotoxicity

Abstract: Alpha-synuclein is a neuronal protein implicated genetically in Parkinson's disease. alpha-synuclein localizes to the nucleus and presynaptic nerve terminals. Here we show that alpha-synuclein mediates neurotoxicity in the nucleus. Targeting of alpha-synuclein to the nucleus promotes toxicity, whereas cytoplasmic sequestration is protective in both cell culture and transgenic Drosophila. Toxicity of alpha-synuclein can be rescued by administration of histone deacetylase inhibitors in both cell culture and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
466
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(506 citation statements)
references
References 59 publications
25
466
2
5
Order By: Relevance
“…More recently, the involvement of deficient epigenetic regulations has also been described, despite the fact that no particular HAT has been implicated in PD. Indeed, in Drosophila, toxic nuclear aggregates of α-synuclein interact with histone H3 and promote its deacetylation, possibly through a histone-"masking" mechanism [104]. Consistent with this result, several studies targeting HDAC members through sodium butyrate or valproic acid have shown an increase in histone acetylation, associated with prosurvival and anti-inflammatory effects, and decreased neurotoxicity markers [105][106][107][108][109][110].…”
Section: Pdmentioning
confidence: 76%
“…More recently, the involvement of deficient epigenetic regulations has also been described, despite the fact that no particular HAT has been implicated in PD. Indeed, in Drosophila, toxic nuclear aggregates of α-synuclein interact with histone H3 and promote its deacetylation, possibly through a histone-"masking" mechanism [104]. Consistent with this result, several studies targeting HDAC members through sodium butyrate or valproic acid have shown an increase in histone acetylation, associated with prosurvival and anti-inflammatory effects, and decreased neurotoxicity markers [105][106][107][108][109][110].…”
Section: Pdmentioning
confidence: 76%
“…Consistent with these findings, the targeted downregulation of SIRT2 has been shown to rescue α-synuclein toxicity and dopaminergic cell loss in flies and in primary mesencephalic culture [31]. Moreover, toxicity associated with nuclear-targeted α-synuclein in both flies and SH-SY5Y cells can be rescued by employing HDAC inhibitors (HDACIs) [22,31,32]. In addition, oxidative stress is known to cause nuclear translocation of α-synuclein, which then binds to the promoter element (peroxisome proliferatorreceptor gamma coactivator-1) PGC1-αto to cause histone deacetylation and lowered PGC1-α levels [33].…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 62%
“…However, studies performed in pharmacologically and genetically manipulated animal models and cell lines that indicate that SNCA expression can be altered by histone modifications. Indeed, in Drosophila models, nuclear-targeted α-synuclein has been shown to bind to histones and reduce histone H3 acetylation through its association with the HDAC SIRT2 [22]. Consistent with these findings, the targeted downregulation of SIRT2 has been shown to rescue α-synuclein toxicity and dopaminergic cell loss in flies and in primary mesencephalic culture [31].…”
Section: Epigenetic Modulation In Familial Parkinson's Diseasementioning
confidence: 65%
See 2 more Smart Citations